2013
DOI: 10.2139/ssrn.2370257
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Air Pollution on Educational Outcomes: Evidence from Chile

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Six of the studies focussed exclusively on primary aged children up to 11 years of age, with two of these studies including participants as young as 6. Two studies included some older students, up to 13 years and 16 years [ 39 , 40 ]. One final study measured overall school performance of ‘K–12′ schools, which covers ages 5–18 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the studies focussed exclusively on primary aged children up to 11 years of age, with two of these studies including participants as young as 6. Two studies included some older students, up to 13 years and 16 years [ 39 , 40 ]. One final study measured overall school performance of ‘K–12′ schools, which covers ages 5–18 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quality scores ranged from two to seven, with an average of 4.6 (see Table 2 ). Seven papers were rated as low quality [ 39 , 40 , 41 , 45 , 47 , 48 , 51 ]. One paper was rated as average quality [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to excessive heat has been tied to risk of cardiovascular diseases, respiratory failure, asthma, and even premature mortality. Studies have also shown that the effects of heat and other environmental exposures can impact the education of students by affecting their cognitive performance and by hindering their learning processes through the exacerbation of respiratory health problems and by causing attention deficit and fatigue [ 4 , 5 , 6 ]. The Republic of Singapore, is a sovereign city-state in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…A brief discussion of the effects of environmental policies may require abstracting from the potential longer-run economic implications of environmental improvements, such as through impacts on sustainability and health, which can have complex effects on each component of GDP per capita, including labour participation and even human capital (Miller and Vela, 2013). Even a relatively simple case, where environmental policy stringency is assumed to increase the relative price of environmental inputs with respect to capital and labour, allows the identification of several potential channels:…”
mentioning
confidence: 99%